2013
DOI: 10.1159/000354463
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Targeted Antioxidant Peptide SS31 Prevents Hypoxia/Reoxygenation-Induced Apoptosis by Down-Regulating p66Shc in Renal Tubular Epithelial Cells

Abstract: Background/Aims: Ischemia/reperfusion injury plays a crucial role in renal transplantation and represents a significant risk factor for acute kidney injury and delayed graft function. Mitochondria-targeted antioxidant peptide SS31 has been shown to attenuate ischemia/reperfusion injury by inhibiting oxidative stress. The present study was carried out to investigate whether the pretreatment of SS31 could reduce hypoxia/reoxygenation (H/R)-induced injury by inhibiting p66Shc. Methods: The cultured rat renal prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…38 SS-31 has proven effective in cultured renal tubular cells in which it preserved mitochondrial structure and accelerated ATP recovery upon reperfusion. 22 We extended these findings to human kidney tissue and found that incubation with SS-31 partially preserved respiratory chain complex I integrity upon simulated I/R. A randomized trial (Evaluation of Myocardial Effects of Bendavia for Reducing Reperfusion Injury in Patients with Acute Coronary Events [EMBRACE] treated for ST-segment elevation myocardial infarction [STEMI]) 24 in which SS-31 was infused in patients with a ST-segment elevation myocardial infarction did not show improved outcome.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…38 SS-31 has proven effective in cultured renal tubular cells in which it preserved mitochondrial structure and accelerated ATP recovery upon reperfusion. 22 We extended these findings to human kidney tissue and found that incubation with SS-31 partially preserved respiratory chain complex I integrity upon simulated I/R. A randomized trial (Evaluation of Myocardial Effects of Bendavia for Reducing Reperfusion Injury in Patients with Acute Coronary Events [EMBRACE] treated for ST-segment elevation myocardial infarction [STEMI]) 24 in which SS-31 was infused in patients with a ST-segment elevation myocardial infarction did not show improved outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, it was observed that mitochondrial damage could be partially rescued by the archetypical mitochondria stabilizing peptide SS-31. 22 The potential of this cardiolipinbinding peptide is extensively shown in preclinical studies 22,23 and the compound has now entered clinical evaluation. 24 …”
mentioning
confidence: 99%
“…When ischemic tissues were reperfused, the plentiful molecular oxygen (O 2 ) reaches the ischemic tissues to form excessive free oxygen radicals, which resulted in extensive apoptosis of tubular epithelial cells and tissue damage [41]. Previous studies showed that reduction of oxidative stress can protect kidney from renal IRI [42]. Zou et al found that pioglitazone protected against renal ischemia-reperfusion injury by increasing the level of enzymatic activities of superoxide dismutase and enhancing antioxidant capacity [43].…”
Section: Discussionmentioning
confidence: 99%
“…ROS that were generated during the HI event caused cell damage not only via direct action on the cell but also via activation of inflammatory pathway (79). We observed an increase in ROS production 12 h after the HI event; this could be because mitochondria are both a source and a target of ROS (78), so after the mitochondrial first injury, there is an increase of ROS production and that can lead to cell death (40).…”
Section: Discussionmentioning
confidence: 82%